Optimal corrective policies under financial frictions - Andreas Schabert (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
This paper examines credit market policies under pecuniary externalities induced by collateral constraints. Pigouvian taxes/subsidies on debt or savings are derived as Ramsey-optimal policies. Firstly, prudential (ex-ante) debt taxes can restore constrained efficiency. Secondly, when policies are non-state and non-time contingent, debt subsidies can be superior to debt taxes. Thirdly, ex-ante saving subsidies are desirable when distributive effects dominate collateral effects. Fourthly, both effects can simultaneously be addressed by non-contingent saving subsidies. The analysis indicates that optimal policies can improve on constrained efficiency and that inefficiencies due to financial externalities can most effectively be addressed by interest rate reductions.
Keywords: E44; G28; H23; 330; Pecuniary externalities; collateral constraint; incomplete markets; Pigouvian policies; inequality